2015
DOI: 10.1002/adfm.201500314
|View full text |Cite
|
Sign up to set email alerts
|

When Nanoparticles Meet Poly(Ionic Liquid)s: Chemoresistive CO2 Sensing at Room Temperature

Abstract: 1wileyonlinelibrary.com oxidizing or reducing gases while operating at room temperature (RT). [16][17][18] Since then, electron conductive polymer-based sensors have attracted rapidly growing interest. [ 19 ] Particularly, the polymers with amino groups have been reported as promising candidates for CO 2 sensing, but in practice they suffer from poisoning with carbamates and therefore failed to fi ll the gap in the CO 2 gas sensor sector. [ 20,21 ] As a consequence, sensing of inert CO 2 gas is still performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 42 publications
2
83
1
1
Order By: Relevance
“…The rare-earth-based materials like perovskites and oxycarbonates, owing to their unique f-electron configuration of Ln (Ln = rare earth) and layered crystal structure, emerge as the most interesting for future photo-and electrochemical applications (3-8). Among rare-earth oxycarbonates (19,20), particularly lanthanum strongly responds to CO 2 and shows up to 16-fold conductivity changes, not seen before for any metal oxides (21). This is very surprising because a direct injection of an electron into CO 2 molecule requires the activation energy of nearly 2 eV (22).…”
mentioning
confidence: 99%
“…The rare-earth-based materials like perovskites and oxycarbonates, owing to their unique f-electron configuration of Ln (Ln = rare earth) and layered crystal structure, emerge as the most interesting for future photo-and electrochemical applications (3-8). Among rare-earth oxycarbonates (19,20), particularly lanthanum strongly responds to CO 2 and shows up to 16-fold conductivity changes, not seen before for any metal oxides (21). This is very surprising because a direct injection of an electron into CO 2 molecule requires the activation energy of nearly 2 eV (22).…”
mentioning
confidence: 99%
“…Extending the works on Ionogel [4] and on composites of MOX with PILs [3], our investigations revealed interesting phenomena occurring upon combining both approaches. Namely, CO2 response which is stronger than reported in literature and also is manifested by increasing resistance, has been observed.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that a variety of gaseous analytes can be detected by ionogel-based sensors, e.g., H2S, ethylene, NO2 and CO2 [2]. A composite material of Poly Ionic Liquid (PIL) with La2O3 was shown by Willa et al [3] to be sensitive to CO2. They ascribed the detection mechanism to a pre-concentration of CO2 by PIL and subsequent detection of CO2 by the La2O2CO3 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Current approaches for CO 2 detection are divided into two mains categories: Non-dispersive infrared technique (NDIR) [2,3] and chemical sensors using resistive [4], capacitive [5] and mass sensitive [6] transducers.…”
Section: Introductionmentioning
confidence: 99%